Os desafios do autismo: uma análise a partir das mídias digitais sobre as pseudotecnologias de cuidado e intervenção - Prado, Nicolle Lima do (Universidade Federal de São Carlos, 2025)
This study aimed to investigate the dissemination of pseudotechnologies for autism care and intervention on digital media platforms in Brazil. To this end, qualitative documentary research was conducted through the analysis of news articles published between September 2023 and October 2024 in widely circulated media outlets. The data were examined using descriptive content analysis. The findings reveal that, despite the guidelines established by the Brazilian Ministry of Health, scientifically unproven interventions—such as the use of chlorine dioxide, fecal transplants, and stem cell therapies—continue to be promoted. These practices exploit the vulnerability of families and expose individuals to significant health risks. Misinformation, amplified by social media and news outlets, undermines access to effective, evidence-based interventions. In light of this scenario, it is essential to regulate and monitor care and intervention practices, as well as to promote awareness strategies and disseminate scientifically grounded information to ensure safe, ethical, and qualified care for autistic individuals and their families.
The challenges of autism: an analysis based on digital media about pseudotechnologies of care and intervention
Keywords: Transtorno do Espectro Autista; Intervenção; Mídias sociais; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL